Charms and chocolate chips eaudiobook - Cates, Bailey (Magical Bakery Mystery, 2013)
Between brewing magically spiced treats at Honeybee Bakery and volunteering with a local conservation group, Katie Lightfoot barely has time to see her firefighter boyfriend, Declan McCarthy, much less delve further into her destiny as a witch. But avoiding her fate won't be as easy as whipping up a new recipe—especially when Katie finds herself once again mixed up in murder. When a fellow volunteer for the conservation group is found dead, Katie's mystical senses tell her that there's more to the death than meets the eye. Her suspicions are confirmed when members of her coven are targeted next. Katie will have to embrace her powers quickly . . . or she may find herself chewed up and spit out by some serious black magic.